2021
DOI: 10.1515/pthp-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Vial coring and fragmentation incidence after angled penetration of rubber stoppers with single-use hypodermic needles

Abstract: Objectives Particles due to fragmentation present a clear risk to the patient. Reported fragmentation rates vary, and an insertion angle at 45°, as opposed to 90°, has been proposed as a mitigation strategy. So, this study evaluated the fragmentation rates induced by single-use hypodermic needles using different angled penetration techniques. Methods Needles underwent fragmentation testing using two penetration techniques. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The bevel-up position induced the least fragmentation, while bevel down with needles >22 gauge yielded the most. Consistent with other studies,35 penetration of rubber stoppers on vials with a blunt needle has a greater incidence of fragmentation and “coring” (parts of the rubber stopper enter the vial) 34. To minimize the risk of coring, it is advised to push through the middle of the bullseye design on the rubber stopper with a 45° angle and bevel up while smoothly and simultaneously rotating the needle to a 90° angle after exiting the underside of the stopper 34.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The bevel-up position induced the least fragmentation, while bevel down with needles >22 gauge yielded the most. Consistent with other studies,35 penetration of rubber stoppers on vials with a blunt needle has a greater incidence of fragmentation and “coring” (parts of the rubber stopper enter the vial) 34. To minimize the risk of coring, it is advised to push through the middle of the bullseye design on the rubber stopper with a 45° angle and bevel up while smoothly and simultaneously rotating the needle to a 90° angle after exiting the underside of the stopper 34.…”
Section: Introductionmentioning
confidence: 58%
“…One study tested 18-, 20-, and 22-gauge needles with bevel facing up, down, and sideways using 2 penetration techniques. 34 The bevel-up position induced the least fragmentation, while bevel down with needles >22 gauge yielded the most. Consistent with other studies, 35 penetration of rubber stoppers on vials with a blunt needle has a greater incidence of fragmentation and “coring” (parts of the rubber stopper enter the vial).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The risk of coring may be reduced by using the smaller needle compared to the larger one, however, seeing this small particle is more difficult [ 7 ]. Another important factor is the bevel position, Rase et al [ 8 ] reported the bevel up position resulted in fewer particles than the bevel down position. To date, there has been no study to compare needle size with the occurrence of particles.…”
Section: Discussionmentioning
confidence: 99%